Virulence plasmid-encoded YopK is essential for Yersinia pseudotuberculosis to cause systemic infection in mice. - Holmström, A (1995)
The virulence plasmid common to pathogenic Yersinia species encodes a number of secreted proteins denoted Yops (Yersinia outer proteins). Here, we identify and characterize a novel plasmid-encoded virulence determinant of Yersinia pseudotuberculosis, YopK. The yopK gene was found to be conserved among the three pathogenic Yersinia species and to be homologous to the previously described yopQ and yopK genes of Y. enterocolitica and Y. pestis, respectively. Similar to the other Yops, YopK expression and secretion were shown to be regulated by temperature and by the extracellular Ca2+ concentration; thus, yopK is part of the yop regulon. In addition, YopK secretion was mediated by the specific Yop secretion system. In Y. pseudotuberculosis, YopK was shown neither to have a role in this bacterium's ability to resist phagocytosis by macrophages nor to cause cytotoxicity in HeLa cells. YopK was, however, shown to be required for the bacterium to cause a systemic infection in both intraperitoneally and orally infected mice. Characterization of the infection kinetics showed that, similarly to the wild-type strain, the yopK mutant strain colonized and persisted in the Peyer's patches of orally infected mice. A yopE mutant which is impaired in cytotoxicity and in antiphagocytosis was, however, found to be rapidly cleared from these lymphoid organs. Neither the yopK nor the yopE mutant strain could overcome the primary host defense and reach the spleen. This finding implies that YopK acts at a different level during the infections process than the antiphagocytic YopE cytotoxin does.